Subglacial Geology and Geomorphology of the Pensacola‐Pole Basin, East Antarctica. (19th June 2019) - Paxman, Guy J. G.; Jamieson, Stewart S. R.; Ferraccioli, Fausto; Jordan, Tom A.; Bentley, Michael J.; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G.
Abstract: The East Antarctic Ice Sheet (EAIS) is underlain by a series of low‐lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola‐Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice‐penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated 500 m below sea level. Gravity and magnetic depth‐to‐source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present‐day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present‐day dynamics of the overlying EAIS. Key Points: We present new compilations of ice thickness, bedrock topography, and gravity anomalies for the Pensacola‐Pole Basin A significant sedimentary succession, 2–3 km in thickness, is preserved beneath the southern part of the basin Basin topography and geology may have influenced the dynamics of past and present‐day ice sheets